FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Felicia, Mungky; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
Corporate Social Responsibility (CSR) is a corporate responsibility not only to its owners or shareholders but also to the relevant stakeholders and / or affected by the existence of the company. The purpose of this study was to determine the effect of firm size, profitability, leverage, and the type of company to the i disclosure policy of i corporate social i responsibility (CSR) to the i companies listed i in Indonesia i Stock i Exchange. The i population of this study is manufacturing companies listed in Indonesia Stock Exchange during the period 2010-2012. Data collected by purposive sampling method, as many as 73 companies obtained a sample of. Analysis using multiple i linear i regression. The analysis i showed that i the variables of firm size, profitability, leverage and influence the type of corporate disclosure policy of Corporate Social Responsibility (CSR) on manufakur companies listed in Indonesia Stock Exchange in the year 2010 to 2012.
Keywords: Corporate Social Responsibility, profitabilitas, leverage, tipe perusahaan